On the Correspondence Between Replacement Cost Income and Economic Income. - Revsine, Lawrence (The Accounting Review, 1970)
The article discusses the issues related to the correspondence between replacement cost income and economic income. The basic concern is centered on the ability of replacement cost income to approximate the results of economic income and thus provide statement users with information concerning changes in the cash flow potentialities confronting a firm. Previous researchers have suggested that theoretical study must precede empirical analysis of the predictive ability of particular income concepts. Since the presupposition of the indirect measurement hypothesis is that replacement cost income is a predictor of economic income, it seems appropriate to investigate the heretofore absent theoretical foundation for this contention. This article illustrates a conceivable inferential error which replacement cost reports might precipitate if Type B and Type C price changes are incorporated. One rationalization for the dissemination of replacement cost reports to investors relies on the validity of the indirect measurement hypothesis. Since investors and other statement users are concerned with firms' cash flow potentialities, it is imperative that accountants develop some external reporting techniques which will satisfy these needs for anticipatory information.